2015
DOI: 10.1371/journal.pone.0145467
|View full text |Cite
|
Sign up to set email alerts
|

Role of Liver X Receptor in AD Pathophysiology

Abstract: Alzheimer's disease (AD) is the major cause of dementia worldwide. The pharmacological activation of nuclear receptors (Liver X receptors: LXRs or Retinoid X receptors: RXR) has been shown to induce overexpression of the ATP-Binding Cassette A1 (ABCA1) and Apolipoprotein E (ApoE), changes that are associated with improvement in cognition and reduction of amyloid beta pathology in amyloidogenic AD mouse models (i.e. APP, PS1: 2tg-AD). Here we investigated whether treatment with a specific LXR agonist has a meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 80 publications
(88 reference statements)
3
28
0
Order By: Relevance
“…Recently, it was reported that activation of LXRs in a triple transgenic mouse model of AD (3xTg-AD) leads to a change in the DNA methylation status of genes related to synaptic function (Syp, Syn1, and Dlg3) and neurogenesis (Hmgb3 and Rbbp7), suggesting an increase in their expression, which was, in fact, confirmed for Syn1 (76). These results are in line with previous work published by the same authors, demonstrating that the beneficial effect of LXR on synaptic function in 3xTg-AD mice is dependent on synaptic-related protein synthesis, which is disrupted by A (77). Another recent study reported that the activation of PPAR by simvastatin is able to improve memory function in 5XFAD mice, which is likely underlined by an increase in cAMP-response element binding protein (CREB) and brain-derived neurotrophic factor (34).…”
Section: Neuronal Functionsupporting
confidence: 90%
“…Recently, it was reported that activation of LXRs in a triple transgenic mouse model of AD (3xTg-AD) leads to a change in the DNA methylation status of genes related to synaptic function (Syp, Syn1, and Dlg3) and neurogenesis (Hmgb3 and Rbbp7), suggesting an increase in their expression, which was, in fact, confirmed for Syn1 (76). These results are in line with previous work published by the same authors, demonstrating that the beneficial effect of LXR on synaptic function in 3xTg-AD mice is dependent on synaptic-related protein synthesis, which is disrupted by A (77). Another recent study reported that the activation of PPAR by simvastatin is able to improve memory function in 5XFAD mice, which is likely underlined by an increase in cAMP-response element binding protein (CREB) and brain-derived neurotrophic factor (34).…”
Section: Neuronal Functionsupporting
confidence: 90%
“…Previous evidence has suggested that RXR and its heterodimer partners are able to regulate the transcription of neuronal genes important for neurogenesis and neurite extension [6770], synaptic function [71], and neuronal survival [1]. A recent study from Sandoval-Hernandez et al reports that treatment of 3xTg-AD mice with LXR agonist GW3965 increases proliferation of neural precursors in the subgranular zone and rescues Aβ-induced deficits in long-term potentiation (LTP) in a protein-synthesis dependent manner [72]. In a later study, Sandoval-Hernandez et al determined that GW3965 treatment was able to effect improved performance on cognitive tests in aged 3xTg-AD mice coincident with reduced DNA methylation in the hippocampus [73].…”
Section: Lxrs In Cns Disordersmentioning
confidence: 99%
“…Deficiency of ABCA1 also decreases ApoE level and impairs ApoE metabolism in brain 3, 5, 2527 . Both ABCA1 and ApoE play a vital role in cholesterol homeostasis, neuronal repair and synaptic plasticity 28, 29 . ABCA1 −B/−B mice are generated by crossing loxP-flanked (floxed) ABCA1 mice with transgenic mice expressing Cre recombinant under the control of the neuronal and glial specific nestin promoter 25 .…”
Section: Discussionmentioning
confidence: 99%
“…GW3965 crosses the blood-brain barrier and stimulates expression of many target genes, including ABCA1/ApoE 6 . GW3965 treatment raises HDL-level in plasma, liver and macrophages 10, 32, 38, 39 , and increases expression of ABCA1/ApoE in the hippocampus and cerebral cortex and rescues hippocampus long-term synaptic plasticity in an Alzheimer’s disease mouse model 29 . In the present study, we found that GW3965-treatment of ABCA1 fl/fl -stroke mice significantly increased the levels of brain-ABCA1/ApoE and blood-HDL, increased gray/WM-remodeling as well as improved functional-outcome.…”
Section: Discussionmentioning
confidence: 99%